2016
DOI: 10.1371/journal.pone.0149678
|View full text |Cite
|
Sign up to set email alerts
|

The Early Worm Catches the Bird? Productivity and Patterns of Trichobilharzia szidati Cercarial Emission from Lymnaea stagnalis

Abstract: Digenean trematodes are common and abundant in aquatic habitats and their free-living larvae, the cercariae, have recently been recognized as important components of ecosystems in terms of comprising a significant proportion of biomass and in having a potentially strong influence on food web dynamics. One strategy to enhance their transmission success is to produce high numbers of cercariae which are available during the activity peak of the next host. In laboratory experiments with 13 Lymnaea stagnalis snails… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 61 publications
3
61
0
Order By: Relevance
“…Parasites of these organisms might alter the distribution and abundance of their hosts, thereby influencing the outcome of ecological assessments. Nevertheless, in most studies on the ecology of free‐living aquatic organisms, parasites are not considered as a factor despite their importance for food‐web structure, biomass and ecosystem integrity (Marcogliese & Cone, ; Marcogliese, ; Lafferty, Dobson & Kuris, ; Dobson, Lafferty & Kuris, ; Kuris et al ., ; Lagrue & Poulin, ; Soldánová, Selbach & Sures, ). These characteristics give parasites key roles in some ecosystems, where they significantly influence the ecological relationships of free‐living species, and thereby modify species diversity and habitat structure (Mouritsen & Poulin, ; Hatcher, Dick & Dunn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Parasites of these organisms might alter the distribution and abundance of their hosts, thereby influencing the outcome of ecological assessments. Nevertheless, in most studies on the ecology of free‐living aquatic organisms, parasites are not considered as a factor despite their importance for food‐web structure, biomass and ecosystem integrity (Marcogliese & Cone, ; Marcogliese, ; Lafferty, Dobson & Kuris, ; Dobson, Lafferty & Kuris, ; Kuris et al ., ; Lagrue & Poulin, ; Soldánová, Selbach & Sures, ). These characteristics give parasites key roles in some ecosystems, where they significantly influence the ecological relationships of free‐living species, and thereby modify species diversity and habitat structure (Mouritsen & Poulin, ; Hatcher, Dick & Dunn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lagrue & Poulin, ). Despite the high snail abundance, overall trematode prevalence in Tomahawk Lagoon is lower than in other systems where infection rates often reach 30% or more in summer (e.g., Preston et al., ; Soldánová et al., ). This further supports the assumption of Lagrue and Poulin () that intermediate host populations in the system are potentially underexploited by parasites and that parasite populations might rather be constrained by other factors, such as transmission dynamics or other epidemiological processes than by limited host resources.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, we converted the individual cercarial body volume into wet mass by multiplication with 1.1 g/cm 3 (Kuris et al., ). This method has been used previously in studies of cercarial productivity (Kuris et al., ; Soldánová et al., ; Thieltges et al., ). However, Llopis‐Belenguer, Blasco‐Costa, and Balbuena () recently showed that such geometric approximation methods lead to a roughly threefold overestimation of the actual volume of trematode flatworms, due to their flattened bodies (see Supporting Information Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations